Absolute Capacitance Measurement by Direct Digital Fitting of Proportional Coefficient - Xuanze Wang; Qian Shi; Da Liu; Boya Xie; Siyuan Chen; Junzhe Luo; Peipei Lu (Applied Sciences)
In the realm of capacitance measurement, traditional methods that gauge capacitance through timing charge and discharge intervals frequently suffer from inaccuracies, particularly due to noise affecting voltage threshold detection. These techniques are also inefficient for high-capacitance components, as their lengthy charge–discharge cycles limit the measurable range within a given period. To this end, a method for directly sampling and analyzing the input and output signals of an RC first-order system under square wave excitation is proposed for a wide range of capacitance measurements. By establishing a proportional relationship between the differentiated output signal and the difference between input and output signals, one can deduce the capacitance. To counteract noise-induced errors during differentiation, data smoothing is applied, enhancing accuracy. This technique achieves a relative standard deviation of less than 0.9% for capacitances from 60 pF to 60,000 pF, using a 100 kΩ reference resistor and continuous square waves. For capacitances above 800 pF, precision further improves to less than 0.2%. The approach leverages least squares fitting and outlier rejection to manage noise effectively. It remains independent of the capacitor’s initial state, ensuring broad-range accuracy and faster measurement times.